Solid electrolyte for secondary battery and method for producing same

By introducing element M and oxygen into the sulfide-based solid electrolyte, its chemical stability and ionic conductivity are improved, the problem of insufficient stability of the sulfide-based solid electrolyte is solved, and efficient ionic conductivity is achieved.

CN119920960APending Publication Date: 2025-05-02ECOPRO BM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411209244.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-31
Filing Date
2024-08-30
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The sulfide-based solid electrolyte has low chemical stability and is easy to react with moisture, resulting in a decrease in ionic conductivity.

Method used

In Li-P-S-X with a crystal structure of sulfur-silver germanium ore, element M (such as strontium or tungsten) and oxygen are introduced to improve ionic conductivity and atmospheric stability through doping of specific substitution rates.

Benefits of technology

The ionic conductivity maintenance rate of solid electrolyte is improved to ensure that the ionic conductivity maintenance rate reaches more than 70% under dry conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides: a solid electrolyte for a secondary battery, which has an argyrodite crystal structure and contains lithium, phosphorus, sulfur, element M, oxygen and halogen elements, the element M being at least one element selected from the group consisting of an element (M2) having an oxidation number of 2 + and an element (M6) having an oxidation number of 6 +, and the element (M6) being at least one element selected from the group consisting of an element (M1) having an oxidation number of 2 + and an element (M6) having an oxidation number of 6 +; the substitution rate DS1 (%) of the element M represented by relational expression 1 is 0.1-1%, and the substitution rate DS2 (%) of the oxygen represented by relational expression 2 is 0.15-2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a solid electrolyte for a secondary battery and a method for producing the same. Background Art

[0002] Lithium-ion secondary batteries currently on the market use electrolytes containing flammable organic solvents, so when a short circuit occurs, there is a possibility of overheating and fire. In response to this, all-solid-state batteries that use solid electrolytes instead of electrolytes are being studied.

[0003] Solid electrolytes are different from liquid electrolytes made of organic matter. Solid electrolytes themselves can function as separation membranes, so existing separation membranes can be removed. In addition, there is no risk of leakage due to side reactions caused by temperature changes or external impacts. In contrast, the absence of electrolytes and separation membranes has the advantage of increasing the ratio of active materials that increase energy density, and can also achieve high-density batteries.

[0004] Solid electrolytes can be roughly divided into three categories: sulfide-based, oxide-based, and polymer-based. Among them, sulfide-based electrolytes can form a wide interface between the electrode and the electrolyte and have the characteristics of high lithium ion conductivity.

[0005] However, the chemical stability of sulfide-based solid electrolytes is relatively lower than that of oxide-based solid electrolytes, so there is a need to improve their stability. Specifically, sulfide-based solid electrolytes are prone to react with moisture in the atmosphere or moisture flowing in during the process due to various factors such as residual Li2S or P2S7 cross-linked sulfur included in the structure. As a result, there are problems in the production process such as reaction with moisture, generation of hydrogen sulfide gas, and reduction of ion conductivity. Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] The purpose of the present invention is to include element M and oxygen in a conventional solid electrolyte of Li-PSX (X = Cl, Br or I) having an argyrodite crystal structure, wherein element M can replace a portion of the Li site, a portion of the P site or both, and oxygen replaces a portion of the S site, thereby synthesizing a solid electrolyte of a new composition while maintaining the argyrodite crystal structure.

[0008] Furthermore, an object of the present invention is to provide a sulfide-based solid electrolyte in which an element M, which is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6), and oxygen are simultaneously included (doped) in an existing sulfide-based solid electrolyte, thereby suppressing the decrease in ionic conductivity caused by doping and improving the ionic conductivity maintenance rate (atmospheric stability).

[0009] Furthermore, an object of the present invention is to provide a sulfide-based solid electrolyte that contains a dopant at a specific substitution ratio and can improve ion conductivity and enhance atmospheric stability.

[0010] Means for solving technical problems

[0011] One example of the present invention provides a solid electrolyte having an Argyrodite crystal structure, containing lithium, phosphorus, sulfur, element M, oxygen and halogen elements, wherein the element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6), and the substitution rate DS1 (%) of the element M represented by the following relationship 1 is 0.1 to 1%, and the substitution rate DS2 (%) of the oxygen represented by the following relationship 2 is 0.15% to 2%.

[0012] Relationship 1: DS1(%)=[M] / ([Li]+[P]+2*[M])×100

[0013] Relationship 2: DS2 (%) = [O] / ( [S] + [O]) × 100

[0014] In Relational Formulas 1 and 2, [Li], [P], [M], [O], and [S] are content ratios of lithium, phosphorus, element M, and oxygen based on the number of atoms, respectively.

[0015] The element M may be strontium (M2), tungsten (M6) or a combination thereof.

[0016] In the solid electrolyte, the substitution ratio DS1-1 (%) of the element M2 represented by the following relational formula 1-1 may be 0.1 to 1%.

[0017] Relationship 1-1: DS1-1 (%) = [M2] / ([Li] + 2 * [M2]) × 100

[0018] In relational expression 1-1, [Li] and [M2] are content ratios of lithium and element M2, respectively, based on the number of atoms.

[0019] In the solid electrolyte, the substitution ratio DS1-2 (%) of the element M6 represented by the following relational formula 1-2 may be 0.1 to 1%.

[0020] Relationship 1-2: DS1-2 (%) = [M6] / ( [Li] + [P] + 2 * [M6]) × 100

[0021] In Relational Formula 1-2, [Li], [P], and [M6] are the content ratios of lithium, phosphorus, and element M6, respectively, based on the number of atoms.

[0022] Another example of the present invention provides a solid electrolyte having an Argyrodite crystal structure, containing lithium, phosphorus, sulfur, element M, oxygen and halogen elements, wherein the element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6), and the solid electrolyte is represented by the following Chemical Formula 1, Chemical Formula 2 or Chemical Formula 3.

[0023] Chemical formula 1: Li 7-2a-c (M2) a PS 6-b-c O b X c

[0024] Chemical formula 2: Li 7-a-c (M6) a P 1-a S 6-b-c O b X c

[0025] Chemical formula 3: Li 7-a1-a2-c (M2) a1 (M6) a2 P 1-a2 S 6-b-c O b X c

[0026] In Chemical Formula 1, Chemical Formula 2 and Chemical Formula 3, X is chlorine, bromine or iodine, 0.005≤a≤0.05, 0.005≤a1+a2≤0.05, 0.005≤b≤0.1, and 1≤c≤2.

[0027] The element M may be strontium (M2), tungsten (M6) or a combination thereof.

[0028] The solid electrolyte may have an ion conductivity of 4.0 mS / cm or more at 25°C.

[0029] The solid electrolyte may have an ion conductivity maintenance rate (%) expressed by the following relational expression 3 of 70% or more after 2 days under dry conditions of an air atmosphere having a dew point of less than -60°C.

[0030] Relation 3

[0031] Ion conductivity maintenance rate (%) = (ion conductivity of solid electrolyte after 2 days / ion conductivity of solid electrolyte after initial synthesis) × 100

[0032] Another embodiment of the present invention provides a method for manufacturing a solid electrolyte, wherein the solid electrolyte is described in claim 1 or 5, and the method for manufacturing the solid electrolyte comprises: a process of mixing a precursor containing lithium, phosphorus, sulfur, and elements M and O; and a process of calcining the mixture.

[0033] The precursor containing lithium, phosphorus, sulfur, and the elements M and O may include at least one selected from WO 3 , BaO, and SrO.

[0034] The sintering process may be performed at a temperature of 400 to 600° C. for 1 to 16 hours in an active atmosphere.

[0035] Still another example of the present invention provides a lithium secondary battery including the above solid electrolyte.

[0036] Effects of the Invention

[0037] The present invention can provide a sulfide-based solid electrolyte with improved ion conductivity and enhanced atmospheric stability. Specifically, a solid electrolyte can be developed with an ion conductivity maintenance rate (%) increased to 70% or more after 2 days under dry conditions of an air atmosphere with a dew point of less than -60°C while ensuring an ion conductivity of 4.0 mS / cm or more at 25°C. DETAILED DESCRIPTION

[0038] The advantages and features of the present invention and methods for achieving the same will be clarified with reference to the embodiments described below. However, the present invention is not limited to the embodiments disclosed below and can be implemented in various forms. These embodiments are only used to complete the disclosure of the present invention and enable ordinary technicians in the technical field to fully understand the scope of the invention. The present invention is only defined according to the scope of the claims.

[0039] Unless otherwise defined, all terms (including technical and scientific terms) used in this specification can be used with the meanings commonly understood by those skilled in the art in the technical field to which the present invention belongs. Throughout the specification, when a part "includes" a structural element, unless there is a special record to the contrary, it means that other structural elements may also be included, rather than excluding other structural elements. In addition, unless otherwise mentioned in a sentence, the singular also includes the plural.

[0040] One example of the present invention provides a solid electrolyte having an Argyrodite crystal structure, containing lithium, phosphorus, sulfur, element M, oxygen and halogen elements, wherein the element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6).

[0041] In the solid electrolyte of the present invention, the ion conductivity and the ion conductivity maintenance rate can be improved. The above-mentioned solid electrolyte is characterized in that, in the previous solid electrolyte containing lithium, phosphorus, sulfur and halogen elements, the element M and oxygen are contained at a specific substitution rate. The element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6). Specifically, the element with an oxidation number of 2+ (M2) can be Sr, and the element with an oxidation number of 6+ (M6) can be W.

[0042] In the conventional solid electrolyte of Li-PSX having the argyrodite crystal structure, when the element M and oxygen are contained, the element M can replace a part of the Li site, a part of the P site, or both, and the oxygen can replace a part of the S site, and a solid electrolyte of a new composition can be synthesized while maintaining the argyrodite crystal structure. When the element M is an element (M2) or Sr with an oxidation number of 2+, one element M2 (Sr) is substituted for two Li (oxidation number 1+), and when the element M is an element (M6) or W with an oxidation number of 6+, one element M6 (W) is substituted for one Li (oxidation number 1+) and one P (oxidation number 5+). And, in the case of oxygen, one oxygen (oxidation number 2-) is substituted for one S (oxidation number 2-).

[0043] When part of lithium and phosphorus is replaced by element M, according to the hard soft acid base (HSAB) theory, the weak acid M and the weak base S (oxidation number is 2-) strongly combine to form MS bonds, thereby inhibiting the reaction of H2O in the atmosphere and improving atmospheric stability.

[0044] On the other hand, when only oxygen is doped, the ion conductivity maintenance rate can be greatly improved, but the ion conductivity may deteriorate sharply. When only the M element is doped, the target effect is not produced and it may be difficult to apply it to products.

[0045] The argyrodite crystal structure is a face-centered cubic structure (FCC) and is included in the space group F-43m. This crystal structure can be confirmed by X-ray diffraction analysis, and when a known X-ray diffraction analysis is applied, there is no particular limitation.

[0046] The present invention provides a solid electrolyte in which the substitution rate DS1 (%) of the element M represented by the following relational formula 1 is 0.1 to 1%, and the substitution rate DS2 (%) of oxygen represented by the following relational formula 2 is 0.15 to 2%.

[0047] Relationship 1: DS1(%)=[M] / ([Li]+[P]+2*[M])×100

[0048] Relationship 2: DS2 (%) = [O] / ( [S] + [O]) × 100

[0049] In Relational Formulas 1 and 2, [Li], [P], [M], [O], and [S] are the content ratios (atomic percentages) based on the number of atoms of lithium, phosphorus, element M, and oxygen, respectively.

[0050] The above DS1 is 0.1 to 1%, for example 0.1 to 0.5%, preferably 0.2 to 0.4%. When the DS1 value is less than 0.1%, the ion conductivity is slightly improved, and on the contrary, when the DS1 value is greater than 1%, the ion conductivity is low and the ion conductivity maintenance rate may be deteriorated.

[0051] The above DS2 is 0.15 to 2%, for example, 0.15 to 1%, 0.15 to 0.7%, 0.5 to 2%, 1.3 to 2%, preferably, 0.2 to 0.7% or 0.6 to 1.5%. When the DS2 value is less than 0.15%, the effect of improving the ion conductivity maintenance rate is negligible. On the contrary, when the DS2 value is greater than 2%, the ion conductivity is low and the ion conductivity maintenance rate is likely to deteriorate.

[0052] On the other hand, DS1 means the ratio (%) of the number of atoms substituted by the M element in the Li site and the P site, and DS2 means the ratio (%) of the number of atoms substituted by the O element in the S site. When part of lithium and phosphorus is substituted by the M element and part of sulfur is substituted by oxygen, the ion conductivity and the ion conductivity maintenance rate can be improved at the same time.

[0053] In the present invention, in the solid electrolyte manufacturing process, MO-doped precursors can be used to replace M and oxygen at the same time. The relationship and numerical range of DS1 and DS2 values ​​can be determined according to the element ratio of M element and O element in the precursor raw material. For example, the above-mentioned MO-doped precursor can be WO3, BaO, SrO, Ta2O5, etc.

[0054] In the solid electrolyte of the present invention, the substitution rate DS1-1 (%) of the above-mentioned element M2 represented by the following relational formula 1-1 can be 0.1 to 1%, for example, 0.1 to 0.6%, preferably, 0.25 to 0.45%. And, the substitution rate DS1-2 (%) of the above-mentioned element M6 represented by the following relational formula 1-2 can be 0.1 to 1%, for example, 0.1 to 0.5%, preferably, 0.2 to 0.4%.

[0055] Relationship 1-1: DS1-1 (%) = [M2] / ([Li] + 2 * [M2]) × 100

[0056] Relationship 1-2: DS1-2 (%) = [M6] / ( [Li] + [P] + 2 * [M6]) × 100

[0057] When the DS1-1 value is less than 0.1%, the improvement in ionic conductivity is negligible. On the contrary, when the DS1-1 value is greater than 1%, the ionic conductivity is low and the ionic conductivity maintenance rate may deteriorate. Moreover, when the DS1-2 value is less than 0.1%, the improvement in ionic conductivity is negligible. On the contrary, when the DS1-2 value is greater than 1%, the ionic conductivity is low and the ionic conductivity maintenance rate may deteriorate.

[0058] On the other hand, DS1-1 means the ratio (%) of the number of atoms replaced by the M2 element in the Li site, and DS1-2 means the ratio (%) of the number of atoms replaced by the M6 ​​element in the Li site and the P site. In metals with an oxidation number of 2+ (M2+) such as Sr, a portion of lithium is replaced by the M2 element, and in metals with an oxidation number of 6+ (M6+) such as W, a portion of lithium and phosphorus are simultaneously replaced by the M6 ​​element.

[0059] The above-mentioned solid electrolyte of the present invention may have an Argyrodite crystal structure, containing lithium, phosphorus, sulfur, element M, oxygen and halogen elements, wherein the above-mentioned element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6), and is represented by the following Chemical Formula 1, Chemical Formula 2 or Chemical Formula 3.

[0060] Chemical formula 1: Li 7-2a-c (M2) a PS 6-b-c O b X c

[0061] Chemical formula 2: Li 7-a-c (M6) a P 1-a S 6-b-c O b X c

[0062] Chemical formula 3: Li 7-a1-a2-c (M2) a1 (M6) a2 P 1-a2 S 6-b-c O b X c

[0063] In Chemical Formula 1, Chemical Formula 2 and Chemical Formula 3, X is chlorine, bromine or iodine, 0.005≤a≤0.05, 0.005≤a1+a2≤0.05, 0.005≤b≤0.1, and 1≤c≤2.

[0064] In Chemical Formulae 1 to 3, M2 is an element having an oxidation number of 2+, and M6 is an element having an oxidation number of 6+. For example, the element M2 may be Sr, and M6 may be W.

[0065] Furthermore, in Chemical Formulae 1 to 3, when the element M is an element with an oxidation number of 2+ (M2) or Sr, one element M2 (Sr) is substituted for two Li (oxidation number 1+), and when the element M is an element with an oxidation number of 6+ (M6) or W, one element M6 (W) is substituted for one Li (oxidation number 1+) and one P (oxidation number 5+). Furthermore, in the case of oxygen, one oxygen (oxidation number 2-) is substituted for one S (oxidation number 2-).

[0066] Furthermore, the above X as a halogen element may be chlorine, bromine or iodine, preferably chlorine. The halogen element may replace a part of the S site, ensure a new path for lithium ions in the lattice, and improve ionic conductivity.

[0067] The solid electrolyte may be 0.005≤a≤0.05, 0.005≤a1+a2≤0.05, 0.005≤b≤0.1, 1≤c≤2, specifically, 0.009≤a≤0.05, 0.01≤a≤0.05, 0.01≤a≤0.03, 0.02≤a≤0.04, 0.009≤a1+a2≤0.05, 0.01≤a1+a2≤0. 05, 0.01≤a1+a2≤0.03, 0.02≤a1+a2≤0.04, 0.009≤b≤0.1, 0.01≤b≤0.1, 0.01≤b≤0.09, 0.01≤b≤0.05, 0.01≤b≤0.03, 0.02≤b≤0.04, 1.2≤c≤1.8, 1.4≤c≤1.6, for example, it can have the composition described in the following Table 1.

[0068] Table 1

[0069]

[0070] The solid electrolyte of the present invention may have an ion conductivity of 4.0 mS / cm or more at 25° C. For example, after the initial synthesis of the solid electrolyte, the ion conductivity may be 4.1 mS / cm or more or 4.2 mS / cm or more. The upper limit value is not particularly limited, but for example, may be 10 mS / cm or less, 7 mS / cm or less, 5 mS / cm or less, or 4.5 mS / cm or less.

[0071] Furthermore, the above-mentioned solid electrolyte, under dry conditions of an air atmosphere with a dew point less than -60°C, after 2 days, the ion conductivity maintenance rate (%) expressed by the following relationship 3 can be 70% or more, for example, 75% or more, 78% or more, or 80% or more. The upper limit value is not particularly limited, but can be below 95% or below 90%.

[0072] Relation 3

[0073] Ion conductivity maintenance rate (%) = (ion conductivity of solid electrolyte after 2 days / ion conductivity of solid electrolyte after initial synthesis) × 100

[0074] Another embodiment of the present invention provides a method for producing a solid electrolyte. The method is not particularly limited, but may include, for example, a step of mixing a precursor containing lithium, phosphorus, sulfur, and elements M and O; and a step of firing the mixture.

[0075] The above-mentioned mixing process is not particularly limited when it is performed by a mixing method known in the art. For example, a mechanical milling method, a melt quenching method, a liquid method, etc. can be applied. As an example, in the case of a mechanical milling method, a compound including Li, P, S, halogens and Sr or W and O as a raw material can be mechanically crushed at a prescribed ratio corresponding to the composition of the target solid electrolyte to obtain a precursor.

[0076] The above-mentioned precursors containing lithium, phosphorus, sulfur, elements M and O and halogens may include Li2S, P2S5, WO3, BaO, SrO and precursors containing halogen elements (X=Cl, Br, I) (LiCl, etc.).

[0077] The calcination process may be performed at a temperature of 400 to 600° C. in an inert atmosphere for 1 to 16 hours, for example, at a temperature of 450 to 600° C., 500 to 600° C., or 530 to 600° C. in an N2 or Ar gas atmosphere for 2 to 16 hours, 2 to 14 hours, or 2 to 12 hours. The conditions of the calcination process are not particularly limited as long as the calcination process is sufficiently performed to form the argyrodite crystal structure of the solid electrolyte.

[0078] Another example of the present invention provides a lithium secondary battery including the above solid electrolyte.

[0079] The lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and the solid electrolyte interposed between the positive electrode and the negative electrode.

[0080] The positive electrode and the negative electrode may be used without particular limitation as long as they are known technologies used in the technical field of lithium secondary batteries.

[0081] Furthermore, the lithium secondary battery may include a battery container (casing) that accommodates an electrode assembly including a positive electrode, a negative electrode, and a solid electrolyte, and a sealing member that seals the battery container.

[0082] At this time, lithium secondary batteries can be classified into can-type lithium secondary batteries in which an electrode assembly is placed in a metal can and pouch-type lithium secondary batteries in which an electrode assembly is placed in a pouch formed of a sheet such as an aluminum laminate, according to the shape of a battery container (casing).

[0083] Hereinafter, the present invention will be described in detail by way of examples. However, these examples are for further explanation of the present invention, and the scope of rights of the present invention is not limited to the following examples.

[0084] Example

[0085] (Mixing process)

[0086] In a dry room (Dry Room) (DP-60°C), lithium precursor Li2S, phosphorus precursor P2S5, chlorine precursor LiCl, and MO precursor (WO3, BaO, SrO, Ta2O5) were weighed in a stoichiometric ratio using a high-energy milling method to obtain the composition shown in Table 2 below.

[0087] Put the precursor with appropriate stoichiometric ratio into a 330ml ZrO2 can, and put in ZrO2 3mm ball which is 10 times the amount of raw materials for fastening.

[0088] Milling was performed using a planetary mill at 330 rpm for a total of 18 hrs.

[0089] (Firing process)

[0090] The mixed product produced in the mixing step is placed in an Al2O3 crucible and then placed in a tube furnace for sintering.

[0091] In order to suppress the reaction with the gas (Gas) present inside the tube furnace, inert N2 gas is flowed in for firing. At this time, the firing conditions are 490°C, the heating rate is 3°C / min, and the holding time is 12 hours. After firing under this condition, it is naturally cooled.

[0092] Experimental example

[0093] (Evaluation method)

[0094] Ionic conductivity

[0095] 200 mg of the solid electrolyte powder of the examples and comparative examples was cold pressed at 4 tons for 2 minutes using a pressure cell measurement mold having a diameter of 10 mm to prepare pellets for ion conductivity measurement, and then AC impedance measurement was performed (applied frequency: 1 MHz-0.01 Hz).

[0096] Ionic conductivity maintenance rate

[0097] After the solid electrolyte powders of Examples and Comparative Examples were exposed in a drying chamber (DP-60° C.) for 48 hours, the ion conductivity was analyzed, and the ion conductivity maintenance rate was calculated according to the following calculation formula.

[0098] Calculation formula: Ionic conductivity maintenance rate (%) = (ionic conductivity after exposure for 48 hours) / (ionic conductivity after synthesis) × 100 (%)

[0099] Table 2

[0100]

[0101] Referring to Table 2, in Examples 1 to 3 and Examples 4 to 6, it was confirmed that when Sr or W and oxygen were doped simultaneously, the ion conductivity was maintained at 4 mS / cm or more and the ion conductivity maintenance rate was improved.

[0102] However, in Examples 7 to 9, when Ba element and oxygen are doped simultaneously, the evaluation result of the ion conductivity maintenance rate is at the level of 80% compared to Sr having the same oxidation number (2+), which is relatively good, but the ion conductivity is less than 4 mS / cm, so the improvement effect is insufficient.

[0103] It was confirmed that when the Sr or Ba substitution rate was higher than 1%, the ion conductivity became lower than that of Ref. (Comparative Example 1), and the ion conductivity maintenance rate was deteriorated.

[0104] On the contrary, in Comparative Examples 2 to 4, it was confirmed that the ion conductivity maintenance rate was improved when only oxygen was doped, but the ion conductivity was at a relatively low level.

[0105] Furthermore, in Comparative Examples 7 to 9, it was confirmed that both the ion conductivity and the ion conductivity maintenance rate decreased when Ta (oxidation number: 5+) and oxygen were doped simultaneously.

[0106] Furthermore, in Comparative Examples 5 and 6, it was confirmed that even if Sr or Ba elements and oxygen were doped simultaneously, when the Sr or Ba substitution rate was greater than 1% and the doping was excessive, the ionic conductivity was lower than that of Ref. (Comparative Example 1) and the ionic conductivity maintenance rate was also inferior.

[0107] As described above, the present invention describes specific embodiments, but it is obvious to a person skilled in the art that the present invention can be modified and varied in many ways without departing from the technical concept of the present invention provided by the appended claims.

Claims

1. A solid electrolyte having a argyrodite crystal structure, containing lithium, phosphorus, sulfur, element M, oxygen and halogen elements, wherein the element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6), the substitution rate DS1 (%) of the element M represented by the following relational formula 1 is 0.1 to 1%, the substitution rate DS2 (%) of the oxygen represented by the following relational formula 2 is 0.15% to 2%, and the solid electrolyte is characterized in that: Relationship 1: DS1(%)=[M] / ([Li]+[P]+2*[M])×100 Relationship 2: DS2 (%) = [O] / ( [S] + [O]) × 100 In Relational Formulas 1 and 2, [Li], [P], [M], [O], and [S] are content ratios of lithium, phosphorus, element M, and oxygen based on the number of atoms, respectively.

2. The solid electrolyte according to claim 1, characterized in that The element M is strontium (M2), tungsten (M6) or a combination thereof.

3. The solid electrolyte according to claim 1, wherein the substitution rate DS1-1 (%) of the element M2 represented by the following relational formula 1-1 is 0.1 to 1%, characterized in that: Relationship 1-1: DS1-1 (%) = [M2] / ([Li] + 2 * [M2]) × 100 In relational expression 1-1, [Li] and [M2] are content ratios of lithium and element M2, respectively, based on the number of atoms.

4. The solid electrolyte according to claim 1, wherein the substitution rate DS1-2 (%) of the element M6 represented by the following relational formula 1-2 is 0.1 to 1%, characterized in that: Relationship 1-2: DS1-2 (%) = [M6] / ( [Li] + [P] + 2 * [M6]) × 100 In Relational Formula 1-2, [Li], [P], and [M6] are the content ratios of lithium, phosphorus, and element M6, respectively, based on the number of atoms.

5. The solid electrolyte according to claim 1, wherein the solid electrolyte is represented by the following Chemical Formula 1, Chemical Formula 2 or Chemical Formula 3, wherein: Chemical formula 1: Li 7-2a-c (M2) a PS 6-b-c O b X c Chemical formula 2: Li 7-a-c (M6) a P 1-a S 6-b-c O b X c Chemical formula 3: Li 7-a1-a2-c (M2) a1 (M6) a2 P 1-a2 S 6-b-c O b X c In Chemical Formula 1, Chemical Formula 2 and Chemical Formula 3, X is chlorine, bromine or iodine, 0.005≤a≤0.05, 0.005≤a1+a2≤0.05, 0.005≤b≤0.1, and 1≤c≤2.

6. A solid electrolyte having an argyrodite crystal structure, containing lithium, phosphorus, sulfur, element M, oxygen and halogen elements, wherein the element M is at least one selected from an element with an oxidation number of 2+ (M2) and an element with an oxidation number of 6+ (M6), and the solid electrolyte is represented by the following chemical formula 1, chemical formula 2 or chemical formula 3, characterized in that: Chemical formula 1: Li 7-2a-c (M2) a PS 6-b-c O b X c Chemical formula 2: Li 7-a-c (M6) a P 1-a S 6-b-c O b X c Chemical formula 3: Li 7-a1-a2-c (M2) a1 (M6) a2 P 1-a2 S 6-b-c O b X c In Chemical Formula 1, Chemical Formula 2 and Chemical Formula 3, X is chlorine, bromine or iodine, 0.005≤a≤0.05, 0.005≤a1+a2≤0.05, 0.005≤b≤0.1, and 1≤c≤2.

7. The solid electrolyte according to claim 6, characterized in that The element M is strontium (M2), tungsten (M6) or a combination thereof.

8. The solid electrolyte according to claim 1, characterized in that The solid electrolyte has an ion conductivity of 4.0 mS / cm or more at 25°C.

9. The solid electrolyte according to claim 1, wherein the ion conductivity maintenance rate (%) expressed by the following relational expression 3 is 70% or more after 2 days under dry conditions of an air atmosphere having a dew point of less than -60°C, wherein the solid electrolyte is characterized in that: Relation 3: Ion conductivity maintenance rate (%)=(ion conductivity of the solid electrolyte after 2 days / ion conductivity of the solid electrolyte after initial synthesis)×100.

10. A method for manufacturing a solid electrolyte, wherein the solid electrolyte is the solid electrolyte according to claim 1 or 5, wherein the method for manufacturing the solid electrolyte comprises: A step of mixing a precursor containing lithium, phosphorus, sulfur and elements M and O; as well as The step of firing the mixture.

11. The method for producing a solid electrolyte according to claim 10, characterized in that: The precursor containing lithium, phosphorus, sulfur, and elements M and O includes at least one selected from WO3, BaO, and SrO.

12. The method for producing a solid electrolyte according to claim 10, characterized in that: The sintering process is performed at a temperature of 400 to 600° C. in an active atmosphere for 1 to 16 hours.

13. A lithium secondary battery, characterized in that: Comprising the solid electrolyte according to claim 1.